Dawn rose on a dead body: armed violence and poppy farming in Mexico - Blazquez, Adèle (California series in public anthropology, 2025)
"Featured prominently in the Netflix series Narcos, Badiraguato is known as the birthplace of Mexico's most notorious criminals, from Caro Quintero to 'El Chapo.' But in this rural community in the Sinaloa sierra, what is the daily life of those invisible in the criminal fresco, who live in this jobless region, grow a tiny patch of poppies, run a grocery store, or hold a position in the local government? Who are the poppy farmers, caught between military repression and exploitation by those who buy their crops? What does it mean to be a woman in a place where men's violence looms? How can people make sense of the killings that punctuate daily life? This sensitive ethnography lifts the veil on a marginalized territory that is the downside of our globalized economy; an ethnography that confronts us with the uncertainty that reigns when once again, 'Dawn rose on a dead body.'"--